Prevalence of periodontal disease in type 2 diabetes mellitus patients: A cross-sectional study - Monika Singh; Vivek Kumar Bains; Rajesh Jhingran; Ruchi Srivastava; Rohit Madan; Shubhash Chandra Maurya; Iram Rizvi (Wolters Kluwer Medknow Publications, 2019)
Aim: The aim of this study was to determine the prevalence of periodontal disease in type 2 diabetes mellitus (T2DM) patients of North India. Materials and Methods: A total of 500 patients fulfilling the selection criteria were initially given a health questionnaire to gather information regarding their demographic characteristics, attitude for oral hygiene, and disease status. Based on eligibility 427 patients were finally recruited for statistical analysis. A partial-mouth periodontal examination (PMPE) protocol which assessed one maxillary quadrant and one mandibular quadrant was used to examine three fixed sites per tooth (mesiobuccal, midbuccal, and distobuccal). Gingival Index, Oral Hygiene Index-Simplified, Debris Index-Simplified, Calculus Index-Simplified (CI-S), probing pocket depth, and clinical attachment level were examined. Results: More than 90% (95.1%) of the total diabetic participants had some degree of periodontal destruction. Of the total population, 27.1% of participants had good oral hygiene, 68.8% had fair oral hygiene, and 3.9% had poor oral hygiene status. The prevalence of severe periodontitis in participants with good, fair, and poor oral hygiene status was reported as 0.8%, 17%, and 29.4%, respectively. The prevalence of severe periodontitis in participants with good, fair, and poor oral hygiene status with poor glycemic control (glycated hemoglobin ≥8%) was 2.5%, 28.1%, and 30.7%, respectively. Conclusion: This single-centered cross-sectional study represents that more than 95% of type 2 diabetic patients have some periodontal destruction. These results may act as baseline data to promote the collaborative integrated management of diabetes for reducing its burden on society.